Adolescents' drinking and drunkenness more likely in one-parent families and due to poor communication with mother - Tomčíková, Zuzana; Veselská, Zuzana Dankulincová; Gecková, Andrea Madarasová; van Dijk, Jitse P; Reijneveld, Sijmen A (Central European journal of public health, 2015)
OBJECTIVES: Alcohol use is a relatively common behaviour, particularly among adolescents, and has become a major public health concern. This study explores the associations between family composition, the quality of adolescents' communication with parents and adolescents' recent frequent alcohol drinking and lifetime drunkenness. METHODS: Data were obtained from the Slovak part of the 2005-2006 Health Behaviour in School-aged Children (HBSC) study. The sample consisted of 3,882 students (46.3% males; mean age 13.3; ± 1.6). Data on drinking alcohol in the past week, lifetime drunkenness, communication and family composition were collected via anonymous questionnaires stratified for ages 11, 13 and 15 years and following the methodology of the HBSC study. RESULTS: The results showed that living in an incomplete family increased the risk of frequent drinking and drunkenness among adolescents as well as a low quality of communication between mothers and their children. Risks were higher for drunkenness than for frequent alcohol use and strongly increased by age, with the communication with parents worsening at increasing age. CONCLUSIONS: Our findings show the importance of the quality of communication between parents and adolescents in preventing the hazardous alcohol use among adolescents. Preventive interventions to reduce adolescents' use of alcohol should therefore also target the quality of communication in the family.
Keywords: Surveys and Questionnaires; Humans; neúplná rodina; chování mladistvých; dítě; Child; Alcohol Drinking; pití alkoholu; Female; Single-Parent Family; lidé; Slovakia; Slovenská republika; průzkumy a dotazníky; Mother-Child Relations; otrava alkoholem; vztahy mezi matkou a dítětem; ženské pohlaví; Communication; Male; Adolescent Behavior; Parenting; Adolescent; komunikace; Alcoholic Intoxication; rodičovství; mužské pohlaví; mladiství